Tradisi Badikia dalam Ritual Managakan Batu Mejan di Nagari Ulakan Kabupaten Padang Pariaman - Ririn Yusliar Rahman; Firdaus Firdaus; Asril Asril (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2021)
This article discusses Badikia tradition in the Managakan Batu Mejan ritual practiced by members of the Syattariyah congregation in Ulakan Tapakis, Padang Pariaman Regency. Badikia tradition are carried out to commemorate 100 days of death. The purpose of the study was to determine the form, structure, and function of the presentation of Badikia in the Managakan Batu Mejan ritual. Using qualitative methods, research data were collected by means of observation, interviews, literature studies, and documentation, to produce analytical descriptions based on theories and conceptual frameworks about rituals. The formulation of the research results shows that Badikia in the Managakan Batu Mejan ritual is a means of religious ritual for followers of the Syattariyah order, which functions to perform sunnah worship by reading sentences of praise to Allah SWT and the Prophet Muhammad SAW, which creates inner satisfaction for the perpetrators.Keyword: Badikia; ritual, Managakan Batu Mejan, Syattariyah; UlakanAbstrakArtikel ini membahas Tradisi Badikia dalam ritual Managakan Batu Mejan yang dipraktikkan oleh jamaah tarekat Syattariyah di  Ulakan Tapakis, Kabupaten Padang Pariaman. Tradisi Badikia dilaksanakan untuk memperingati 100 hari kematian. Tujuan penelitian adalah untuk mengetahui bentuk, struktur, serta fungsi dari penyajian Badikia dalam ritual Managakan Batu Mejan. Menggunakan metode kualitatif, data penelitian dikumpulkan dengan teknik observasi, wawancara, studi pustaka, dan dokumentasi, untuk menghasilkan deskripsi bersifat analitik berdasarkan teori dan kerangka konseptual tentang ritual. Formulasi hasil penelitian menunjukkan bahwa Badikia dalam ritual Managakan Batu Mejan merupakan sarana ritual agama bagi pengikut tarekat Syattariyah, yang berfungsi untuk melakukan ibadah sunah dengan cara membacakan kalimat puji-pujian kepada Allah SWT dan Nabi Muhammad SAW, yang menimbulkan kepuasan bathin bagi pelakunya.Kata Kunci: Badikia; ritual; Managakan Batu Mejan; Tarekat Syattariyah; Ulakan